The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/sleep/zsac079.365
|View full text |Cite
|
Sign up to set email alerts
|

0368 Leveraging the Electronic Health Record to Facilitate Shared-Medical Decision Making in a Large Health System: Response to the PAP Recall

Abstract: Introduction The positive airway pressure (PAP) device manufacturer recall afflicting ~4 million users has posed a major challenge for the care of patients with sleep disordered breathing. We report on the Cleveland Clinic enterprise-wide response efforts and relevant predictors of medical decision-making surrounding this recall. Methods A taskforce developed a strategic response to the recall with the goal of distributing en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One report examined whether recalled PAP devices could be modified to reduce risks (Rabec et al, 2022). In our domain of organizational case studies, we found two accounts, one from Mayo Clinic (Morgenthaler et al, 2022) and one from the Cleveland Clinic (Lance et al, 2022).…”
Section: Introduction Nature Of Problem Being Addressedmentioning
confidence: 97%
“…One report examined whether recalled PAP devices could be modified to reduce risks (Rabec et al, 2022). In our domain of organizational case studies, we found two accounts, one from Mayo Clinic (Morgenthaler et al, 2022) and one from the Cleveland Clinic (Lance et al, 2022).…”
Section: Introduction Nature Of Problem Being Addressedmentioning
confidence: 97%